Special Education in Rural Mexico: Two Schools in Jalisco - Favela, Alejandra; Petteys, Phyllis (Journal of the American Academy of Special Education Professionals, 2022)
This article provides an overview of current special education policy in Mexico and highlights two successful schools in rural Jalisco that have garnered recognition as particularly creative and responsive institutions. A void exists in the literature about the types of specialized services that children with disabilities are likely to encounter south of the border. U.S. educators can maximize the success of their Mexican origin special needs students, by having a better understanding of this schooling context. The topic of this paper is of particular urgency to a record number of families who are facing voluntary or involuntary deportation, and who are concerned about access to quality services for their differently abled children, particularly if they find themselves in rural communities.